Agents’ & vendors’ satisfaction toward distribution services at Utusan Melayu (M) Berhad/ Ema Izzaila Ibrahim - Ibrahim, Ema Izzaila (Faculty of Business and Management, 2010)
The purpose of the study is to identify weather agents or vendor that distribute newspapers from Utusan satisfy with the services that were provided by the company. It also will help the company to find which factors from logistics, management and relationship that most influence agents’ and vendors’ satisfaction. The first step to find the result is to find as much as possible information about the Utusan, vendors, agents and services. Additional and relevant information is also obtained from journals, books, magazine, and internet. After that, all possible and relevant information from sources mention earlier are gathered and analyzed with the combination of the existing information at the Customer Service Department at Utusan. To create questionnaire, several questions are made according to the utusan services and agents or vendors satisfaction. Next step after the questionnaire is completed is to distribute and ask the questions to the agents or vendors for them to answer. The selected agents or vendors are contacted through phone. All the answer are recorded and used for analysis and discussion later. From the result obtained, it can be concluded that most of the agents and vendors satisfy with the utusan especially in term of relationship and followed by its management and lastly it’s logistic. Thus, it is relevant to say that generally vendors and agents are satisfied with the services provided by Utusan.